Returns management in a business–to–business context: its impact on customer satisfaction. (3rd January 2014) - Vachon, Stephan; Hajmohammad, Sara; Patry, Karine
Managing the returns process effectively can lead to cost reduction and revenues increase even if it is often considered as a peripheral activity in the supply chain. This paper investigates the relation between returns management and customer satisfaction in a business–to–business (B2B) context. Building on the inter–organisational justice perspective, a model that links the characteristics of the returns management system, the system performance, and customer satisfaction is developed. The proposed conceptual model was tested using data collected through a survey of 192 heating, ventilation, air conditioning and refrigeration (HVAC–R) contractors in Canada. Results indicate that: i) the level of administrative support provided by the suppliers to assist the contractors (i.e., the customers) with the returns process is predominant in generating the customer satisfaction; ii) the performance of returns management system is significantly and positively linked to customer satisfaction. Implications for future research and managers are also discussed.